Femoral Approach: an Exceptional Alternative for Permanent Pacemaker Implantation - Valente, B (2014)
The classic transvenous implantation of a permanent pacemaker in a pectoral location may be precluded by obstruction of venous access through the superior vena cava or recent infection at the implant site. When these barriers to the procedure are bilateral and there are also contraindications or technical difficulties to performing a thoracotomy for an epicardial approach, the femoral vein, although rarely used, can be a viable alternative. We describe the case of a patient with occlusion of both subclavian veins and a high risk for mini-thoracotomy or videothoracoscopy, who underwent implantation of a permanent single-chamber pacemaker via the right femoral vein.